2020
DOI: 10.1111/ele.13537
|View full text |Cite
|
Sign up to set email alerts
|

Sick plants in grassland communities: a growth‐defense trade‐off is the main driver of fungal pathogen abundance

Abstract: Aboveground fungal pathogens can substantially reduce biomass production in grasslands. However, we lack a mechanistic understanding of the drivers of fungal pathogen infection and impact. Using a grassland global change and biodiversity experiment we show that the trade-off between plant growth and defense is the main determinant of infection incidence. In contrast, nitrogen addition only indirectly increased incidence via shifting plant communities towards faster growing species. Plant diversity did not decr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
137
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(161 citation statements)
references
References 97 publications
9
137
3
Order By: Relevance
“…Secondly, we show that less conserved leaf traits like leaf magnesium content and stomata size are important in determining foliar fungal pathogen richness and infestation, besides other commonly-found phylogenetically conserved traits, that are linked to the growth-persistence tradeoff, such as leaf habit and specific leaf area (Cappelli et al, 2020;Kembel & Mueller, 2014). With this our results urge future studies to include a wide range of leaf traits, including phylogenetically conserved and less conserved leaf traits to better predict foliar fungal pathogen richness and infestation.…”
Section: Resultsmentioning
confidence: 81%
“…Secondly, we show that less conserved leaf traits like leaf magnesium content and stomata size are important in determining foliar fungal pathogen richness and infestation, besides other commonly-found phylogenetically conserved traits, that are linked to the growth-persistence tradeoff, such as leaf habit and specific leaf area (Cappelli et al, 2020;Kembel & Mueller, 2014). With this our results urge future studies to include a wide range of leaf traits, including phylogenetically conserved and less conserved leaf traits to better predict foliar fungal pathogen richness and infestation.…”
Section: Resultsmentioning
confidence: 81%
“…Our prediction that biodiversity loss underlies the dilution effect was grounded in host community competence, because host communities become more competent as biodiversity is lost (e.g., Johnson et al ., 2013; Liu et al ., 2017); however, biodiversity loss could also influence the dilution effect by other potential mechanisms. As an example, biodiversity loss does not necessarily alter nutrient availability in the same way that nutrient availability influences biodiversity, with implications for higher trophic levels (Grace et al ., 2016; Cappelli et al ., 2020). Gradients that are or are not associated biodiversity loss could also differ in host abundance or density, connectivity of hosts and parasites, or host temporal turnover (Keesing et al ., 2006, 2010; Young et al ., 2014; Johnson et al ., 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that specialist soil pathogens can drive diversity-productivity relationships by reducing biomass particularly at low diversity 23,24 . In our experiment, foliar pathogen impact was not reduced in (untreated) high diversity communities, perhaps due to a shift towards generalist pathogens 51 or because increased spillovers of pathogens (between species) counteracted resource concentration effects in diverse mixtures 52 . The absence of an effect of foliar fungal removal on biodiversity-multifunctionality relationships suggests that resources are more important context drivers than foliar enemies, but changes in other enemy groups or in foliar fungal species composition still need to be investigated further.…”
Section: Discussionmentioning
confidence: 57%
“…The plots were sprayed with two fungicides to try to achieve broad suppression of the fungal community (“Score Profi”, 24.8 % Difenoconazol 250 g.L −1 and “Ortiva”, 32.8% Chlorothalonil 400 g.L −1 6.56% Azoxystrobin 80 g.L −1 ) four times during the growing season (beginning of April and June, late July and September) and the same amount of water was applied to the untreated plots. The fungicides were very effective in suppressing rusts and mildews but less effective in reducing infection by leaf spots, and had very few non target effects 51 . The experiment was weeded three times a year to maintain the diversity levels.…”
Section: Methodsmentioning
confidence: 99%